Activated bentonite promoted Friedländer condensation reactions: Synthesis of thieno[2,3-b]quinolinones and tacrines analogues derivatives - Dridi, Khaireddine Mohamed; Said, Ridha Ben; Arfaoui, Youssef; Al-Ayed, Abdullah Sulaiman (European Journal of Chemistry, 2013)
Some new aminothieno[2,3-b]quinolinones and tacrine analogues derivatives were synthesized in high yield with acid activated bentonite as a catalyst via the Friedländer condensation reactions between 2-aminothiophene-3-carbonitrile and ketones. The structure elucidation of compounds was done by FT-IR, NMR spectroscopy and microanalytical elemental data.